Psychometric properties of the EATQ-R among a sample of Catalan-speaking Spanish adolescents (2015)
The few studies that have been conducted into the psychometric properties of the EATQ-R, even fewer for the longer version, highlight the fact that its structure differs from that of the original. The aim of this study is to translate and adapt the long version of the EATQ-R to Catalan, study its internal consistency and convergent and factorial validity, and compare differences in the EATQ-R by age and gender. The EATQ-R was administered to a sample of 1481 secondary school students ranging in age from 11 to 17 years. After eliminating 40 items from the 86 comprising the EATQ-R, an adjusted model was obtained with acceptable fit indices comprising 8 of the original 11 factors.